Protective effects of curcumin on diabetic nephropathy via attenuation of kidney injury molecule 1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL) expression and alleviation of oxidative stress in rats with type 1 diabetes - Ghasemi, Hassan (Iran J Basic Med Sci, 2019)
OBJECTIVE(S): One of the serious complications of Type1 diabetes (T1D) is diabetic nephropathy, which is accompanied with overexpression of kidney injury molecule 1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL) and enhanced oxidative stress. The present study was conducted to examine the protective effect of curcumin on the expression of KIM-1, NGAL genes and oxidative damage in the kidney of T1D rats. MATERIALS AND METHODS: Thirty-six adult male rats were divided into 6 groups (n=6). The control and T1D groups received treatment with curcumin or without it (80 and 130 mg/kg, respectively). After 60 days of treatment, using spectrophotometric methods, biochemical factors and oxidative stress markers were measured. Gene expression of KIM-1 and NGAL was evaluated using quantitative PCR. Also, plasma and urine levels of these two proteins were assayed by the ELISA kit. RESULTS: Diabetes caused a significant increase in the levels of creatinine, FBS, uric acid, urea, and creatinine in the serum, which were attenuated after the administration of curcumin. There was a significant reduction in the values of creatinine, uric acid, and urea in urine in the diabetic group whereas in the rats treated with curcumin, these values were normalized to the normal level (especially in 130 mg/kg). Curcumin administration had a significant role in modulation of serum lipid profile, and it was shown to decrease the kidney and urinary expression levels of KIM-1 and NGAL genes and improve oxidative toxic stress in the kidney tissues. CONCLUSION: Curcumin can play a protective role in reducing the unpleasant consequences of diabetic nephropathy.